Pirolisis Biomassa Kayu Pinus (Wood Pine) Dengan Katalis Mo/Lempung Menjadi Bio-Oil - M Arfi Adharyandy Firman; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Indonesia high dependence on fossil fuels from year to year makes the conditions of dwindling fossil fuel reserves. This condition implies the need to optimize the use of renewable energy in order to maintain the availability of energy in the future. An alternative of renewable energy and eco friendly bio-oil. Bio-oil can be produced by pyrolysis process of the pine wood biomass with a Mo/Clay catalyst. This research examines the influence of variations containing Mo (0%, 1%, 2% and 3% w/w) and variations in the weight of the catalyst, Mo/clay (3%, 5% and 7% w/w) in the pyrolysis determine fir wood into bio-oil against the yield obtained and determine the physical and chemical properties of the bio-oil produced from pine wood pyrolysis process. In this research, pine wood biomass, as much as 50 grams with a size of 100 mesh, silinap 500 ml, and the catalyst Mo/clay incorporated in the pyrolysis reactor. Pyrolysis is carried out at 320oC and 300 rpm stirring speed for 120 minutes carried out by flowing nitrogen gas (N2) as an inert gas. The results showed that the optimum yield 61.89% was obtained on the catalyst, Mo/Clay 5% w/w with Mo metal content of 3% w/w. The result of the physical and chemical properties, obtained by the density (0.967 g / ml), viscosity (6.459 cSt), acidity (105.282 mg NaOH / g sample) and flash point (48oC). The results of chemical composition analysis by GC-MS, chemical components of the dominant acquired bio-oil m methylcyclohexyl bromide 9.42%, 3-butene-1,2-diol, 1- (2-furyl) - 6.95%, 2,2,3,3-tetramethyl butane 6.12%, cis-2,2-dimethyl-4-decene and 4.58% 1-propene, 2-methyl, tetramer 3.78%Keywords: Biomass, bio-oil, Mo/ clay catalyst, wood pine, pyrolysis